Money and Coinage in the Middle Ages - Naismith, Rory (Brill, 2018)
This volume is the first in a new series entitled Reading Medieval Sources, examining different genres of sources in the Middle Ages, and this book focuses on ways of studying medieval money, and the most direct manifestation of money: coinage. It is intended to introduce readers to a range of approaches to a subject that has, traditionally, been seen as somewhat specialised domain of highly technical study which often seems to sit at some remove from the mainstream of historical and archaeological research. One important aim of the chapters offered is to show ways in which money can be incorporated into analysis of the Middle Ages more broadly, both for particular periods and in specific thematic contexts such as art, literature and economic analysis.